Design and control of an x-y-θz parallel piezoelectric nanopositioning stage with a large moving platform. (February 2023) - Wang, Bowen; Cui, Yuguo; Yang, Yiling; Xie, Qifang; Chen, Pan
This paper introduces the design and control of a new type of x - y -θ z parallel piezoelectric nanopositioning stage. Using the spatial cross-distributed double parallel four-bar linkage (DPFL), the mirror symmetrically distributed driving unit and auxiliary unit are designed. Then, a parallel piezoelectric nanopositioning stage with a large moving platform and good guidance and decoupling performance are designed. The workspace and frequency response characteristics of the stage are analyzed based on the stiffness and dynamic models. To improve the static and dynamic characteristics of the stage, the structural size is optimized, and the optimization results are verified by Finite Element Analysis (FEA). To reduce the response time, hysteresis nonlinearity, and external disturbance of the stage, a compound controller combining a rate-dependent Prandtl–Ishlinskii (PI) hysteresis compensator and a proportional-integral controller is designed. Finally, the prototype of the stage is made by Wire Electro-Discharge Machining (WEDM) technology. The open-loop performance of the stage is tested experimentally. The results show that the maximum relative coupling error between x and y directions is less than 0.5%. Also, the experimental control results show that the designed compound controller has a fast response speed, good positioning, and tracking performance.